Repeated Evolution of Identical Domain Architecture in Metazoan Netrin Domain-Containing Proteins - Leclère, Lucas (Oxford University Press, 2012)
The majority of proteins in eukaryotes are composed of multiple domains, and the number and order of these domains is an important determinant of protein function. Although multidomain proteins with a particular domain architecture were initially considered to have a common evolutionary origin, recent comparative studies of protein families or whole genomes have reported that a minority of multidomain proteins could have appeared multiple times independently. Here, we test this scenario in detail for the signaling molecules netrin and secreted frizzled-related proteins (sFRPs), two groups of netrin domain-containing proteins with essential roles in animal development. Our primary phylogenetic analyses suggest that the particular domain architectures of each of these proteins were present in the eumetazoan ancestor and evolved a second time independently within the metazoan lineage from laminin and frizzled proteins, respectively. Using an array of phylogenetic methods, statistical tests, and character sorting analyses, we show that the polyphyly of netrin and sFRP is well supported and cannot be explained by classical phylogenetic reconstruction artifacts. Despite their independent origins, the two groups of netrins and of sFRPs have the same protein interaction partners (Deleted in Colorectal Cancer/neogenin and Unc5 for netrins and Wnts for sFRPs) and similar developmental functions. Thus, these cases of convergent evolution emphasize the importance of domain architecture for protein function by uncoupling shared domain architecture from shared evolutionary history. Therefore, we propose the terms merology to describe the repeated evolution of proteins with similar domain architecture and discuss the potential of merologous proteins to help understanding protein evolution.